2006
DOI: 10.1016/j.jhsb.2006.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Cold Intolerance of the Hand Measured By the Ciss Questionnaire in a Normative Study Population

Abstract: Cold intolerance has been recognized as one of the most disabling sequelae of upper extremity trauma, especially when neurovascular structures are involved. In this study, we aimed to describe cold intolerance in a normative study population, validate the Cold Intolerance Symptom Severity (CISS) questionnaire and define the threshold for abnormal cold intolerance. One hundred and eight volunteers participated in our study. In addition to the CISS score, information about age, gender and previous surgery or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 17 publications
1
105
2
1
Order By: Relevance
“…Irwin et al showed that patients with a complete median or ulnar nerve injury and a vascular injury had more severe cold intolerance [19]. In healthy uninjured subjects, Ruijs et al found that neither gender nor age was associated with symptoms of cold intolerance [37]. Traynor and MacDermid compared cold water immersion assessment and patientreported questionnaires in healthy uninjured subjects [42].…”
Section: Discussionmentioning
confidence: 99%
“…Irwin et al showed that patients with a complete median or ulnar nerve injury and a vascular injury had more severe cold intolerance [19]. In healthy uninjured subjects, Ruijs et al found that neither gender nor age was associated with symptoms of cold intolerance [37]. Traynor and MacDermid compared cold water immersion assessment and patientreported questionnaires in healthy uninjured subjects [42].…”
Section: Discussionmentioning
confidence: 99%
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The CISS was designed to evaluate the patient's sensitivity to exposure to cold 27,28 . The item scores are summed for a total score ranging from 0 to 100; higher scores indicate greater cold sensitivity.…”
Section: Short-form Mcgill Pain Questionnaire (Sf-mpq)mentioning
confidence: 99%
See 2 more Smart Citations